INVESTIGATING TEACHERS’ TEACHING METHODS USED IN READING CLASSROM - Enni Erawati Saragih; Umia Ulfa Zalya (ENGLISH, 2019)
To achieve better knowledge, students are expected to be able to read some books in a week. But nowadays, reading no longer becomes student’s habit. It seems because teachers teaching method is still need to be modified in order to get students attention and interest. This research aims to find out the methods used by the teacher in teaching reading and student response on the method. The research adopted descriptive-qualitative research method and in collecting the data observation and interview were used as the instruments of the research. After doing the research, the data found that there are two kinds of method are used by the teacher while he/she teaches reading classroom, namely; direct method and language experience approach (LEA). Meanwhile, the student response toward teacher reading method shown that most of students like teachers reading method, only few students dislike about teachers teaching methods.